285. Challenging the Dogmas of Outpatient Parenteral Antimicrobial Therapy Through a Randomized Controlled Trial. (26th November 2018) - Ibrahim, Laila; Hopper, Sandy; Orsini, Francesca; Daley, Andrew; Babl, Franz; Bryant, Penelope
Abstract: Background: Outpatient parenteral antimicrobial therapy (OPAT) has shifted from being a novel concept to an accepted model of care for some conditions. However, concerns remain that have limited its broader roll out: the use of daily ceftriaxone regarding its efficacy and impact on antibiotic resistance, intravenous (IV) catheter complications, risk of treating an acute infection directly from the emergency room (ER), and concern that OPAT has shifted the burden of cost from hospitals to patients. We aimed to address these questions with the first randomized controlled trial (RCT) of OPAT efficacy in children: comparing OPAT directly from the ER using IV ceftriaxone with hospitalization using IV flucloxacillin for moderate/severe cellulitis. Methods: The RCT was set at a tertiary pediatric hospital from January 2015 to June 2017. Inclusion criteria: children 6 months–18 years with uncomplicated cellulitis needing IV antibiotics. Patients were randomized to ceftriaxone via OPAT at home or flucloxacillin in hospital, using a peripheral catheter. Primary outcome: treatment failure within 48 hours due to lack of improvement or adverse events. Secondary outcomes: complications, readmission, acquisition of nasal and stool-resistant bacteria and costs. Results: A total of 188 children were randomized: 93 to OPAT and 95 to hospital. In the intention-to-treat population, there was no difference in treatment failure between OPAT and hospital (2% vs. 7%, P = 0.09). Per protocol, OPAT had less failure (1% vs. 8%, P = 0.03). There was no increased acquisition of MRSA, ESBL, VRE or C. difficile with OPAT compared with in hospital at 1 week or 3 months ( P > 0.05). Complication rates were similar (6% vs. 7%, P = 0.78), and repeat IV catheterization was less with OPAT (3% vs. 15%, P = 0.002). Readmission was 1% on OPAT. The cost to families was significantly less with OPAT (AUD213 vs. AUD733, P < 0.001). Conclusion: Despite the acuity of the infection, OPAT with IV ceftriaxone for moderate/severe cellulitis in children is efficacious with complications and readmissions no different from hospital care with IV flucloxacillin. Short-term ceftriaxone use in healthy children on OPAT is not associated with increased acquisition of resistant organisms, and has reduced burden of costs to families (ClinicalTrials.gov NCT02334124). Disclosures: All authors: No reported disclosures.